2017
DOI: 10.3233/jcb-179004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro skin three-dimensional models and their applications

Abstract: Abstract. Skin fulfils a plethora of eminent physiological functions ranging from physical barrier over immunity shield to the interface mediating social interaction. Prone to several acquired and inherited diseases, skin is therefore a major target of pharmaceutical and cosmetic research. The lack of similarity between human and animal skin and rising ethical concerns in the use of animal models have driven the search for novel realistic three-dimensional skin models. This review provides a survey of contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 104 publications
0
61
0
Order By: Relevance
“…• Afferents are further classified into Aβ, Aδ and C nerve fibres with defined roles in the skin related to their action-potential propagation speed, a function of their degree of myelination 20,27,65 • Secrete neuropeptides, neurotrophins, neurohormones 8,39,40 • Sensation, touch, response to mechanical, chemical or thermal stimuli, 'nociception' 9,40,65 • Pain, neurogenic-inflammation 6,28,40 • Vascular regulation, vasodilation via sensory nerves, vasoconstriction via neuropeptide signalling 8 Adipocytes Hypodermis • Absorbs mechanical loads, insulates 10 • Mediates fibroblast recruitment during wound healing 89 • Energy source responsible for triglyceride production 90 • May function as endocrine organ through secretion of growth factors, hormones and cytokines to communicate with the rest of the NIC/NICE systems, associated with lipid metabolism and other metabolic processes 89 17 UV-induced immune events 25 and sensitization. 26 These models contributed useful information towards the understanding of skin pathologies including atopic dermatitis, cancers or drug development.…”
Section: Skin Cell Type or Component Location(s) Function(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…• Afferents are further classified into Aβ, Aδ and C nerve fibres with defined roles in the skin related to their action-potential propagation speed, a function of their degree of myelination 20,27,65 • Secrete neuropeptides, neurotrophins, neurohormones 8,39,40 • Sensation, touch, response to mechanical, chemical or thermal stimuli, 'nociception' 9,40,65 • Pain, neurogenic-inflammation 6,28,40 • Vascular regulation, vasodilation via sensory nerves, vasoconstriction via neuropeptide signalling 8 Adipocytes Hypodermis • Absorbs mechanical loads, insulates 10 • Mediates fibroblast recruitment during wound healing 89 • Energy source responsible for triglyceride production 90 • May function as endocrine organ through secretion of growth factors, hormones and cytokines to communicate with the rest of the NIC/NICE systems, associated with lipid metabolism and other metabolic processes 89 17 UV-induced immune events 25 and sensitization. 26 These models contributed useful information towards the understanding of skin pathologies including atopic dermatitis, cancers or drug development.…”
Section: Skin Cell Type or Component Location(s) Function(s)mentioning
confidence: 99%
“…The proper differentiation of cells. 10,24,60 In summary, the most important considerations for the design of an optimal skin biomaterial would be the following: mechanically robust and/or flexible to allow for skin movement, biodegradable at controlled rate to optimize integration with cells or the local tissue (for implants), bio-inertness of the scaffold, conductivity to aid neural integration and/or reintegration, and additional factors to promote healing to enhance neural regrowth and/or wound healing. 24,61 A crucial avenue of skin research, and of relevance to the innervation field, is wound healing.…”
Section: Con Clus I On S and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, however, it is difficult to ensure wounds that are equal in size using this method [63], and thus for this reason, testing of pharmaceutical products on these types of cultures are not ideal. 2D skin cell cultures also lack essential functions that could mimic in vivo processes, such as immune functionality and blood perfusion [65]. 3D wound healing models have thus attempted to more closely mimic in vivo wound healing processes and are available as histocultures or HSEs.…”
Section: Skin Cell Cultures For Wound Healingmentioning
confidence: 99%
“…Given the relatively time-efficient protocols, reduced use of lab resources, and control over culture parameters, spheroids prove useful for investigation into skin applications. Due to the historical success of sheet-based skin models ( Figure 16), few research groups have developed skin spheroids [79], [80]. Some research groups have found success combining KRTs with dermal fibroblasts in a dual culture system [79].…”
Section: Tissue Engineered 3d Skin Culturementioning
confidence: 99%